2021
DOI: 10.1108/ijchm-07-2020-0705
|View full text |Cite
|
Sign up to set email alerts
|

Tit for tat: understanding the responding behavior of property hosts on peer-to-peer rental platforms

Abstract: Purpose Due to their very different contexts, the responses made by property hosts to online reviews can differ from those posted by hotel managers. Thus, the purpose of this study is to investigate the determinants of the responding behavior of hosts on peer-to-peer property rental platforms. Design/methodology/approach This study applied a comprehensive framework based on the theory of planned behavior. Empirical models are constructed based on 89,967 guest reviews with their associated responses to reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…First, our work contributes to the P2P accommodation platform literature by highlighting the importance of the listing popularity. The extant P2P accommodation platform literature has largely centered on the investigation of reservation behavior (So et al , 2018; Nisar et al , 2020), loyalty behavior (Shuqair et al , 2019; So et al , 2019), participation behavior (Lee et al , 2019), host behaviors (Liang et al , 2021), pricing strategy (Sainaghi, 2020) and P2P accommodation performance (Leoni et al , 2020; Ranjbari et al , 2020). However, the listing popularity has been largely underexplored in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our work contributes to the P2P accommodation platform literature by highlighting the importance of the listing popularity. The extant P2P accommodation platform literature has largely centered on the investigation of reservation behavior (So et al , 2018; Nisar et al , 2020), loyalty behavior (Shuqair et al , 2019; So et al , 2019), participation behavior (Lee et al , 2019), host behaviors (Liang et al , 2021), pricing strategy (Sainaghi, 2020) and P2P accommodation performance (Leoni et al , 2020; Ranjbari et al , 2020). However, the listing popularity has been largely underexplored in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…user-generated photos) in consumer decision-making, such as restaurant selection (Oliveira and Casais, 2019) and hotel booking intention (Ladhari and Michaud, 2015). The second stream focuses on explaining the host behaviors of P2P accommodation (Li et al , 2020; Xie and Chen, 2019; Liang et al , 2021; Kim et al , 2021; Teixeira et al , 2020). The third stream highlights the pricing strategy of P2P accommodation (Gibbs et al , 2018; Sainaghi, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The peer profile can be a starting point for peers to interact and co-create value for one another. According to previous researchers (Casais et al , 2020; Foroudi et al , 2019; Liang et al , 2021), peers may co-create by interacting during service encounters, outlining their preferences, expectations, reviews, likes and dislikes. A pleasant profile that shows trustworthiness (Shen et al , 2020), good reputation and appealing content (Li, 2019;) encourages value co-creation between peers (Kim et al , 2021; Prebensen and Xie, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most findings are consistent with those of studies on users’ motivation for sharing knowledge in online communities, such as Q&A forums and internet encyclopedias. However, given the particularities of online review provision, some studies also reported that reciprocity is ineffective in influencing users’ review provision because online reviews benefit a broad range of audiences rather than specific individuals (Ke et al , 2020; Liang et al , 2021). Most related studies tended to investigate the determinants of users’ review-posting behavior from the perspective of verifying the effectiveness of platform incentive strategies (Bortoluzzi et al , 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%